Stochastic Models of Behavior - Horvath, William J. (Management Science, 1966)
The Management scientist must understand the various processes leading to regularities in human behavior. When man-machine combinations are involved such regularities are usually a consequence of the mechanical limitations of the machinery. Less well known but equally important are certain statistical regularities which appear in mass behavior. Recent research in the societal sciences has demonstrated behavioral regularities in such diverse fields of human endeavor as information processing, problem solving, group interactions and learning. The underlying cause behind these observed phenomena is not always obvious but can be ascribed partly to limitations in the human organism and partly to the structuring of the environment in which the behavior is observed. Whatever the theoretical basis for the observed behavior, the regularities provide the management scientist with the necessary predictability of behavior needed for his studies. Two examples of recent research in this area are discussed in this paper. One is a group formation model proposed by Coleman and James and the second is a group interaction model first studied by Bales. Both of these are representative of a broad class of models which the management scientist should be able to incorporate in his work.